Perancangan Game Batik “Nitiki” Berteknologi Multi-Touch Screen - Chandra Tresnadi; Irfansyah Irfansyah; Ary S. Prihatmanto (Journal of Visual Art and Design, 2008)
Batik is an intangible cultural heritage of Indonesia that has endured a span of 200 years in its existence. Batik may enter today’s contemporary world by exploiting both the traditional and contemporary cultures to look beyond what has been elaborated before. Having exposed to the world of digital game and animation, this study exploited multi-touch screen technology to develop a new game-play on Javanese batiks as a visual entertainment medium to serve learning of batik. Using gesture interactivity sensors, the game of batik was designed by allowing users to interact freely with the contents limiting the mechanistic control in game playing. The end-result showed that traditional artifact, such as batik, can be exposed in a new technological medium. The game of batik serves as an alternate way to suit traditional knowledge into the contemporary world we live in.